Hemocompatibility-related Adverse Events Following HeartMate II Left Ventricular Assist Device Implantation between Japan and United States - Teruhiko Imamura; Minoru Ono; Koichiro Kinugawa; Norihide Fukushima; Akira Shiose; Yoshiro Matsui; Kenji Yamazaki; Yoshikatsu Saiki; Akihiko Usui; Hiroshi Niinami; Goro Matsumiya; Hirokuni Arai; et al. (Medicina, 2020)
Background: Left ventricular assist device (LVAD) therapy has improved the clinical outcomes in advanced heart failure patients, however, this may differ between countries. We aimed to compare outcomes between Japanese and US LVAD cohorts. Methods: For 416 consecutive LVAD patients who received HeartMate II LVAD implantation and completed a one-year follow-up, age-matched Japanese patients (the Japanese registry for mechanically assisted circulatory support (J-MACS) group) and the US patients were compared for their clinical outcomes. Results: 154 J-MACS patients and 77 US patients were compared. Survival, free from hemocompatibility-related adverse events (HRAEs) in the J-MACS was statistically comparable with the US (75% vs. 63%, p = 0.79). J-MACS had more disabling strokes than the US (0.221 vs. 0.052/patient-year, p = 0.005), whereas there was less nonsurgical bleeding (0.045 vs. 0.117/patient-year, p = 0.024). The net hemocompatibility score was statistically comparable between the groups (1.54 vs. 1.19 points/patient, p = 0.99). Post-LVAD prothrombin time with international normalized ratio (INR) <1.5 (odds ratio 4.07) was a risk factor for HRAEs in J-MACS, whereas INR >3.0 (odds ratio 5.71) was a risk factor in the US (p < 0.05 for both). Conclusion: In the age-matched cohorts, the J-MACS group experienced more strokes, while the US group had more bleedings. “Tailor-made” therapeutic strategy might be required for each country, given the unique variation of HRAE incidence among each country.